2006
DOI: 10.1590/s1806-83242006000300004
|View full text |Cite
|
Sign up to set email alerts
|

In vitro minocycline activity on superinfecting microorganisms isolated from chronic periodontitis patients

Abstract: Chronic periodontitis is the most common type of periodontitis and it is associated with various species of microorganisms. Enteric rods, Pseudomonas, Staphyloccocus and Candida have been retrieved from periodontal pockets of patients with chronic periodontitis and correlated to cases of superinfection. Local or systemic antibiotic therapy is indicated to reinforce the effects of the conventional mechanical therapy. Minocycline has been suggested as one of the most effective drugs against periodontal pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
(27 reference statements)
1
20
0
1
Order By: Relevance
“…The small number of drugs available for fungal treatment, most of which are fungistatic, and the emerging resistance to antifungal agents encourage the search for alternative treatments (de Oliveira et al, 2006). Plants are good options for obtaining a wide variety of drugs and have been used in medicine for a long time; in particular, they are extensively used in folk medicine because they represent an economic alternative, are easily accessible and can be applicable to various pathologies (Sardi et al, 2011;Cruz et al, 2007).…”
Section: Candida Biofilm and New Antifungal Strategiesmentioning
confidence: 99%
“…The small number of drugs available for fungal treatment, most of which are fungistatic, and the emerging resistance to antifungal agents encourage the search for alternative treatments (de Oliveira et al, 2006). Plants are good options for obtaining a wide variety of drugs and have been used in medicine for a long time; in particular, they are extensively used in folk medicine because they represent an economic alternative, are easily accessible and can be applicable to various pathologies (Sardi et al, 2011;Cruz et al, 2007).…”
Section: Candida Biofilm and New Antifungal Strategiesmentioning
confidence: 99%
“…Plants are good options for obtaining a wide variety of drugs [5,6] (Table 1). Another promising antifungal strategies are Silver nano particles (interfere with microbial DNA replication within bacteria and fungi), Anti-Candida antibodies (can reduce the binding of Candida to various surfaces), Photodynamic therapy (inactivation of the fungus) and Gold nano particle conjugate (mediated photodynamic therapy may be used against nosocomially acquired refractory C albicansbiofilms) [7][8][9][10].…”
Section: Candida Biofilm and New Antifungal Strategiesmentioning
confidence: 99%
“…Oliveira and coworkers performed in vitro minocycline activity on superinfecting microorganisms isolated from chronic periodontitis patients and the minimum inhibitory concentration (MIC) of microorganisms were found in the range as: Enterobacteriaceae (4-16 μg/ml), strains of Staphylococcus spp. (0.25-8 μg/ml), Pseudomonas aeruginosa (64-128 μg/ml) and Candida genus between (0.25-16 μg/ml) [36]. Clinical trials on subgingival minocycline in chronic periodontitis subjects showed that the scaling followed by subgingival minocycline is effective in reducing periodontal pathogens in chronic periodontitis [37,38].…”
Section: Characteristics Of Minocycline Hclmentioning
confidence: 99%